A Comprehensive and Effective Mass Spectrometry-Based Screening Strategy for Discovery and Identification of New Brassinosteroids from Rice Tissues - Xin, Peiyong; Yan, Jijun; Li, Bingbing; Fang, Shuang; Fan, Jinshi; Tian, Hailong; Shi, Yong; Tian, Weisheng; Yan, Cunyu; Chu, Jinfang (Frontiers in Plant Science, 2016)
The exploration and identification of new brassinosteroid (BR) compounds is critical to improve the biosynthetic research of BRs and expand the chemodiversity of active BRs. However, traditional methods are labor-intensive, time-consuming, and less sensitive. Here, we present a facile screening strategy for discovering and identifying novel BRs from plant tissues based on ultra performance liquid chromatography-mass spectrometry (UPLC-MS). A total of 14 potential BRs were discovered from only 1 g of rice tissues and structurally elucidated by following a MS-based clue, acquired through multiple reaction monitoring (MRM) data-dependent enhanced product ion (EPI) scan, high resolution MS, and MS survey-dependent MS/MS. One of the 14 candidates was identified as 6-deoxo-28-homotyphasterol, a brand new BR compound that is reported for the first time in the BRs biosynthesis pathway. Detailed comparison with reference standards and quantitative level analysis in rice BRs mutants confirmed the availability of the other candidates. This effective, yet simple method provides an efficient way to find more and more chemically new BR biosynthetic intermediates in plants, which is significant for complementing the biosynthesis and metabolism network of BRs. This strategy may also be used to discover unknown compounds of other plant hormone species as well as their key metabolites.